Mass customization information systems in business - Blecker, Thorsten; Friedrich, Gerhard (Idea Group Reference, 2007)
"This book describes original, innovative works on IT systems for mass customization, and provides a multitude of solutions, tools, concepts and successful realizations of IT systems for mass customization. It discusses state-of-the-art mass customization while depicting the importance of IT in making the strategy function efficiently in order to support the business processes required for manufacturing individualized products"--Provided by publisher.
Keywords: Flexible manufacturing systems.; Product management.; Customer relations.; Consumers' preferences.; elektronické knihy; electronic books